The effects of exercise on the immune system and stress hormones in sportswomen - Karacabey, K; Saygin, O; Ozmerdivenli, R; Zorba, E; Godekmerdan, A; Bulut, V (Maghira & Maas Publications, 2005)
BACKGROUND: Despite the numerous studies controversial results exist in specific immune response to exercise. The aim of this study was to determining the differences in the humoral immune parameters, serum ACTH and cortisol levels existing between sportswomen and sedentary subjects and the effect of acute aerobic and anaerobic exercise on these parameters. MATERIALS/METHODS: 40 sportswomen (Groups I and 2) and 20 sedentary women (Group 3) were enrolled and Group I performed aerobic exercise on a treadmill for 30 minutes while the Group 2 was subjected to the Wingate effort test for 30 seconds. Before exercising (at 8.30 a.m), immediately after the exercise, and 4 hours, days 2 and 5 days after exercising blood samples were obtained and the levels of IgA, IgG, IgM, complement 3 (0) and complement 4 (C4) were determined turbidometrically. RESULTS: Before exercise: the means of IgA and IgG values in the G1 and G2 groups were higher than the Group G3, and the mean cortisol levels in the sedentary group was significantly higher (p < 0.05). After Exercise: Whereas the C3 and C4 levels decreased significantly at the end of the exercise in Group I and 2 (p < 0.05), the IgA, IgG (p < 0.05) and IgM levels (p < 0.01) at the 4th and 5th determinations were observed to be significantly higher in only the Group 1. The cortisol and ACTH levels were found to have increased significantly (p < 0.05) in the Group 1. In Group 2, no changes were observed in the IgA, IgG and IgM levels. CONCLUSIONS: We conclude that regular and moderate exercise has favorable effects on the immune system by increasing immunoglobulines which are potent protective factors.
Keywords: exercise; immune system; stress hormones; immunoglobulines